Saving sharks by nudging change - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2014)
In a commentary, SMU Associate Professor of Law and an ‘I’m FINished with FINS’ campaign ambassador Eugene Tan welcomed Parliament’s passing of the Animals and Birds (Amendment) Bill. He commented that the Bill, which seeks to enhance the welfare and responsible care of animals, is important as he felt that our treatment of non-human beings, which share the same space we do, speaks equally to what we are as a society as well as our sense of well-being and responsibility to creatures unable to protect themselves. Citing the silent, unfolding phenomenon of the declining popularity of shark’s fin soup in Singapore, Associate Prof Tan noted that the various ‘Say No to Shark Fin’ campaigns by different groups and individuals are instructive. He felt that this mindset shift enabling the change of embedded cultural and dietary habits speaks volumes of how the broad campaign is slowly but surely contributing to the delicacy’s declining popularity.